Not All Scientists Are Equal: Role Aspirants Influence Role Modeling Outcomes in STEM. Issue 3 (3rd May 2020) - Hu, Danfei; Ahn, Janet N.; Vega, Melissa; Lin-Siegler, Xiaodong
Abstract: Three experiments examined how role aspirants' (i.e., people exposed to role models) views of scientists' exceptional talent affected motivation. Study 1 demonstrated that when exposed to a scientist whose success is associated with effort (i.e., Thomas Edison), rather than inborn talent (i.e., Albert Einstein), role aspirants' motivation increased. Study 2 found that role aspirants benefitted less from exposure to Einstein than to a non-famous scientist. Study 3 replicated and supplemented Studies 1 and 2 by further examining the directionality of motivation. Exposure to Einstein and Edison had opposing effects on motivation relative to a non-famous scientist, due to the different views role aspirants hold of their success. These results suggest that role aspirants are critical in determining role modeling outcomes.